Basic Islamic Economics and Finance Education among Youth at Raudhatul Ulum Senior High School Sakatiga Ogan Ilir, South Sumatera - Widyanata, Fera; Suhel; Farla, Wita; Syathiri, Ahmad; Marissa, Feny (Universitas Pendidikan Ganesha, 2023)
This community service targeted the youth audience, particularly the students of Raudhatul Ulum Senior High School Sakatiga, Ogan Ilir Regency, South Sumatra Province. This school was selected because Islamic Economics and Finance education has not been included in the learning curriculum, whereas it is located in a boarding school complex. Thus, the students have lack knowledge about Islamic Economics and Finance. The youth was targeted because they are a generation that is currently active, enthusiastic and productive. The aims of this community service is that local youth as agents of change can implement the principles and concepts of Islamic Economics in their daily life, family and community to build economic progress in their village. The methods used in the implementation of community service are socialization, education, and workshops. From the results of this community service activity, it can be concluded that the knowledge and interest of teenagers in Islamic Economics and Finance have increased significantly so that they can practice it in their various daily economic activities whilst conveying it to other people, to create a prosperous Islamic economic environment.